(untitled) (Journal of the Bangladesh Agricultural University, 2011)
Ten layer farms (eight from Manikganj and two from Gazipur) were selected to evaluate the effect of the different environmental condition on layer performance. Temperature (°C) and relative humidity (%) were recorded and concentrations of carbon dioxide (CO2, ppm) and ammonia (NH3, ppm) were determined. Productive performance of flock was evaluated by measuring egg production, feed consumption, egg weight and egg shell thickness. The tolerable temperature for the layer was 15-27°C. High temperature (above 27°C) affects feed consumption, egg weight and egg shell thickness while relative humidity has less impact on egg production, egg weight and feed consumption. Feed consumption and egg weight were decreased markedly when CO2 and NH3 concentration were more than 3000 and 37 ppm, but not on egg shell thickness. Postmortem examination indicated that 51, 24, 11, 9 and 5% birds were died due to bacterial, viral, non-infectious, protozoal and fungal infection respectively. Improper environments reduced the chickens’ defenses, making them more vulnerable to diseases. Keywords: Temperature; Humidity; CO2; NH3; Layer performance DOI: 10.3329/jbau.v8i2.7934 J. Bangladesh Agril. Univ. 8(2): 253-258, 2010